A simplified growing model for mixed black locust (Robinia pseudoacacia L.) and poplar (Populus spp.) plantations in the Danube-Tisza Interfluve - Rédei, Károly; Ábri, Tamás (Acta Agraria Debreceniensis, 2023)
This study presents a static model of mixed black locust (Robinia pseudoacacia L.) plantation stand structures for inventory stand structures between 10 and 40 years of age. Due to its local character, the model can be advantageous in planning tending operations, making structural factor predictions for the standing stock (main stand) after tending cuts, and preparing local wood production and silvicultural models. The model data presented in this paper show that poplars account for 55–62 % of the volume per hectare due to their faster growth rate in mixed black locust and poplar plantations. Maintaining the black locust part of the stand necessitates harvesting the poplars by the age of 10 at the latest.